The effects of teaching programming with scratch on pre-service information technology teachers' motivation and achievement - Erol, Osman; Kurt, Adile Aşkım (Computers in human behavior, 2017)
The aim of this study is to examine the effect of programming instruction with Scratch on student motivation and their programming achievements. The study group consisted of 52 sophomore students attending the Department of Computer Education and Instructional Technologies of Mehmet Akif Ersoy University's Faculty of Education, Turkey. Participants were randomly divided into two groups in order to have 26 students in both the test group and the control group. During the first seven weeks of the study, it is aimed that the students will understand programming logic and learn basic programming structures. For this purpose, participants in the test group were instructed using Scratch, whilst in the control group, flowcharting and problem-solving activities were conducted as per the curriculum. During the second seven weeks of the study, C# programming language instruction was conducted using the same method for both the test and control groups. Achievement Test and Motivated Strategies for Learning Questionnaire were utilized as data collection tools in the study, and a 3 × 2 (measurement time x groups) factorial design was employed. Study findings revealed that programming achievement scores for both the test and control groups increased at the end of the whole process; however, the increase was significantly different in favor of the test group at the end of the whole process. It was observed that motivation scores decreased in the control group, while the test group's scores increased. •Flow chart activities decrease participants' motivation.•Scratch activities increase participants' motivation.•The rise of motivation continue during C# instruction process.•Scratch activities are more effective in improving the programming achievements then flowcharts activities.